Navigating the delicate balance of autonomy and harmony: a case study on the cultural adaptation of palliative care interventions in China - Tong Zuo; Seng Yen Yeap; Guijun Lu (BMC Palliative Care)
Abstract Background The implementation of palliative care in China faces distinct challenges influenced by cultural and societal factors that significantly affect terminally ill patients and their families. This case study examines how palliative care interventions adapted to Chinese cultural factors such as death taboos, indirect communication styles, family-centered decision-making, and relational harmony helped empower a patient’s autonomy, facilitate self-expression, and support personal transformation while aligning with Chinese cultural norms. Methods This retrospective study utilized Interpretative Phenomenological Analysis (IPA) to conduct a thorough qualitative investigation of a single case, focusing on how a Chinese terminal cancer patient engaged with and responded to culturally adapted palliative care interventions. The data encompassed notes and audiovisual materials produced throughout the patient’s palliative care process, supplemented by targeted retrospective data collection. The data, originally in Chinese, were translated into English for analysis, using back-translation and independent verification to maintain linguistic and cultural accuracy. Results This study identified three critical mechanisms through which culturally adapted palliative care enhanced the patient’s autonomy and facilitated personal transformation while maintaining relational harmony. The three mechanisms were: (1) a guided card game facilitating autonomous decision-making, (2) spiritual dialogues facilitating self-discovery and transformation, and (3) a communal concert balancing individual expression with relational harmony. Together, these mechanisms empowered the patient to assert personal autonomy and attain meaningful self-expression, all while maintaining significant involvement from family and community. Conclusions This study underscores the critical role of cultural adaptation in implementing palliative care interventions for Chinese patients. The findings demonstrate that culturally adapted palliative care interventions, grounded in relational autonomy, effectively supported a Chinese patient’s autonomy and personal transformation while maintaining relational harmony. These insights are instrumental in informing the provision of culturally adaptive end-of-life care practices in Chinese healthcare.